Juvenile Onset Huntington's Disease - Nopoulos, Peggy C. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The Special Issue "Juvenile Onset Huntington's Disease" highlights the growing interest in understanding the unique aspects of this ultra-rare disorder. After decades of research, gene therapy trials are underway for Adult Onset Huntington's Disease (AOHD). However, patients with Juvenile Onset Huntington's Disease (JOHD) are often excluded from these efforts, leaving many questions regarding its phenomenology. The current issue includes seven articles spanning work on the difficult emotional experiences of parents of children with JOHD; a review of the clinical manifestations of JOHD; behavioral issues in JOHD; CAG repeat and age of motor onset; autonomic nervous system dysfunction; and abnormality in MRI metabolic markers. Finally, a review of the therapeutic advances is included, highlighting future possibilities of clinical trials in JOHD subjects. The HD community-patients, family members at-risk for HD, caregivers, health-care professionals and scientists-is keen on expanding our understanding of JOHD. In the flurry of research on AOHD, those with JOHD were seemingly 'left behind.' The study of patients who are afflicted early in life with HD has become imperative, with this Special Issue representing just the beginning of the required effort to address this urgent need.